Effects of maturation and size on population pharmacokinetics of pentoxifylline and its metabolites in very preterm infants with suspected late‐onset sepsis or necrotizing enterocolitis: a pilot study incorporating clinical outcomes. Issue 1 (16th November 2018) - Salman, Sam; Hibbert, Julie; Page‐Sharp, Madhu; Manning, Laurens; Simmer, Karen; Doherty, Dorota A.; Patole, Sanjay; Batty, Kevin T.; Strunk, Tobias
Abstract : Aims: Infection‐induced inflammation is associated with adverse long‐term outcomes in preterm infants. Pentoxifylline (PTX) is a candidate for adjunct immunomodulatory therapy in preterm infants with late‐onset sepsis (LOS) and necrotizing enterocolitis (NEC), but pharmacokinetic data in this population are extremely limited. This study aims to characterize the pharmacokinetic properties of intravenous PTX and its metabolites in preterm infants. Method: An open label pilot clinical study of intravenous PTX as an adjunct therapy in preterm infants (gestation <32 weeks) with suspected LOS or NEC was undertaken. PTX was infused for 12 h for two days (60 mg kg −1 per 12 h), and in infants with confirmed diagnosis of LOS or NEC, for 6 h for another 4 days (30 mg kg −1 per 6 h). Plasma concentrations of PTX and its principal metabolites from collected blood samples were measured using a validated LCMS assay. NONMEM was used to analyse the data using population pharmacokinetic modelling. Results: The preterm infants ( n  = 26) had a median (range) gestation of 24.8 weeks (23.3–30.4) and birthweight of 689 g (370–1285). PTX was well tolerated and without treatment‐limiting adverse effects. Changes in size (weight) and maturation were successfully modelled for PTX and metabolites. After allometric scaling, clearance increased with postmenstrual age, increasing by approximately 30% per week for PTX and M1 (lisofylline) and simulations of current dosing demonstrated a six‐fold difference in exposure between 24 and 35 weeks postmenstrual age. Conclusions: The developed model can be used to explore dosing strategies based on size and maturation for preterm infants. Abstract :